INDONESIA'S EFFORT TO FACE INDIA'S DUMPING ACCUSATIONS OF CHEMICAL PRODUCTS HYDROGEN PEROXIDE FROM 2016 TO 2017 - Alasta, Mitha Putri; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This paper aims to explain the efforts of the Indonesian government to deal with India’s dumping accusations of chemical products hydrogen peroxide from 2016 to 2017. Hydrogen peroxide is an export commodity that is used for various industries such as textiles, food, pulp and paper. In 2016 India accused Indonesia of dumping hydrogen peroxide exported to its country and would impose anti-dumping duties if proven dumping. According to the theory of Neoliberal Institutionalism, the state is an important actor in international relations. Each country interacts using regional and international dialogue and cooperation mechanisms through bilateral or multilateral forums. Indonesia and India have approached bilaterally in resolving accusations dumping of chemical products hydrogen peroxide. This study uses the perspective of Neoliberalism, which believes that the state or government supports free trade, so the government must remove trade barriers to international trade. There are two results from this study that explain the efforts of the Indonesian government to deal with accusations of India’s dumping of chemical products hydrogen peroxide from 2016 to 2017. The first is an internal effort, that is the Indonesian government advocating for companies accused of dumping. The second is an external effort, that is the defense of the Indonesian government in the form of submitting a rebuttal/opinion at the Oral Hearing/Public Hearing. The settlement of this trade conflict is carried out by bilateral negotiations between Indonesia and India. Keywords: dumping, hydrogen peroxide, India, Indonesia.